A toy or a friend? Children's anthropomorphic beliefs about robots and how these relate to second‐language word learning - Berghe, Rianne; Haas, Mirjam; Oudgenoeg‐Paz, Ora; Krahmer, Emiel; Verhagen, Josje; Vogt, Paul; Willemsen, Bram; Wit, Jan; Leseman, Paul (Journal of computer assisted learning, 2021)
This study investigates the degree to which children anthropomorphize a robot tutor and whether this anthropomorphism relates to their vocabulary learning in a second‐language (L2) tutoring intervention. With this aim, an anthropomorphism questionnaire was administered to 5‐year‐old children (N = 104) twice: prior to and following a seven‐session L2 vocabulary training with a humanoid robot. On average, children tended to anthropomorphize the robot prior to and after the lessons to a similar degree, but many children changed their attributed anthropomorphic features. Boys anthropomorphized the robot less after the lessons than girls. Moreover, there was a weak but significant positive correlation between anthropomorphism as measured before the lessons and scores on a word‐knowledge post‐test administered the day after the last lesson. There was also a weak but significant positive correlation between the change in anthropomorphism over time and scores on a word‐knowledge post‐test administered approximately 2 weeks after the last lesson. Our results underscore the need to manage children's expectations in robot‐assisted education. Also, future research could explore adaptations to individual children's expectations in child‐robot interactions. Lay Description What is already known about this topic Children tend to anthropomorphize robots Standardized tests for anthropomorphism are not suitable for young children What this paper adds Children's overall anthropomorphism score stays the same over seven one‐on‐one sessions with a robot. Children attribute more cognitive abilities to the robot and fewer mechanical properties over time Gender and age are related to changes in anthropomorphism Children's anthropomorphism is (weakly) correlated with their learning performance. Implications for practice and/or policy A first step towards a validated questionnaire about children's anthropomorphism of robots The robot's apparent cognitive abilities seem to play a role in a human‐like perception of the robot over time In the future, perception of the robot can be taken into consideration when designing robot‐assisted tutoring sessions.